DNA‐binding specificity and RNA polymerase inhibitory activity of bis(aminoalkyl)anthraquinones and bis (methylthio) vinylquinolinium iodides - William O. Foye (2018)
The determination of DNA‐binding specificities for a series of bis(methylthio)vinylquinolinium iodides and two bis(aminoalkyl)‐anthraquinones was accomplished by spectral analysis, equilibrium dialysis, elevation of melting temperature, and inhibition of DNA function as a template for Escherichia coli RNA‐polymerase transcription activity in vitro. Studies of complex formation were carried out by comparison of difference spectra of the compounds in the presence of native double‐stranded DNA and separated‐strand DNA. Base specificity of the interaction between DNA and the compounds was demonstrated for both series, particularly for the anthraquinones, for the guanine‐cytosine base pair. Comparison of the difference spectra of the compounds in the presence of DNA with varied base‐pair ratios showed a strong preference of the anthraquinones for the guanine‐cytosine base pair, but the quinolinium compounds showed no preference. The linear‐binding isotherm for the quinolinium compounds indicated one type of binding site, while two types of binding sites were apparent for the anthraquinones. Since only one anthraquinone was active in leukemia tests, factors other than DNA binding must account for the activity of the antileukemic derivative. Copyright © 1982 Wiley‐Liss, Inc., A Wiley Company